Comparative Analysis of Fiber Characteristics and Chemical, Physical, and Mechanical Properties of Six Indigenous Bamboo Species from Indonesia - Sarah Augustina; Riana Anggraini; Ika Yuliandari; Antalina Florida br Marpaung; Feby Savva Charisma; Muhammad Rasyidur Ridho; Pati Kemala; Seng Hua Lee; Apri Heri Iswanto; Petar Antov; Widya Fatriasari (BioResources)
Bamboo is a versatile, sustainable resource used in industries such as construction, furniture, textiles, and paper. Its species vary in properties, influencing their suitability for specific applications. This research aimed to perform a comparative analysis of the fiber characteristics and chemical properties of Indonesian bamboo species from the genera Gigantochloa, Schizostachyum, and Bambusa. Pearson’s correlation analysis was performed to quantify associations among fiber characteristics, chemical composition, and mechanical performance. The results indicated that Bambusa presented the greatest fiber density, whereas Gigantochloa presented superior fiber dimensions, and Schizostachyum presented intermediate values. The mechanical properties of the fibers were inversely related to density. Bambusa showed the highest fiber dimensions, followed by Schizostachyum, whereas Gigantochloa presented the lowest scores, with the exception of the flexibility ratio. All the species, notwithstanding their variation, satisfied the criteria for fiber quality class II. The Bambusa species presented the highest contents of holocellulose, α-cellulose, and hemicellulose, followed by Gigantochloa and Schizostachyum. The highest concentration of starch was found in Schizostachyum, followed by Gigantochloa, and then Bambusa. Notably, G. serik, S. brachycladum, and B. blumeana have demonstrated considerable potential for pulp and paper applications, similar to traditional pulpwood species.